2021
DOI: 10.1093/carcin/bgab088
|View full text |Cite
|
Sign up to set email alerts
|

Early dynamics of circulating tumor DNA predict chemotherapy responses for patients with esophageal cancer

Abstract: We investigated whether early circulating tumor DNA (ctDNA) changes, measured using digital PCR (dPCR), can predict later chemotherapy responses in esophageal squamous cell cancer (ESCC). We compared the dynamics of ctDNA and tumor volumes during chemotherapy in 42 ESCC. The accuracy of predictions of later chemotherapy responses were evaluated by the ratio of the variant allele frequency (VAF) of ctDNA (post-/pre-ctDNA) and the total tumor volume (post-/pre-volume) before and after an initial chemotherapy cyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…31 We previously demonstrated that, in contrast to next-generation sequencing (NGS), frequent ctDNA monitoring by dPCR enabled early relapse prediction, treatment efficacy evaluation, and disease-free corroboration in the management of gastrointestinal cancers, including CRC. [32][33][34][35] Here, we examined results of ctDNA assays from over 1,500 plasma samples and found that ctDNA monitoring by dPCR can provide early relapse detection and disease-free corroboration at molecular level during postoperative CRC surveillance as compared to conventional CTS and CEA monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 We previously demonstrated that, in contrast to next-generation sequencing (NGS), frequent ctDNA monitoring by dPCR enabled early relapse prediction, treatment efficacy evaluation, and disease-free corroboration in the management of gastrointestinal cancers, including CRC. [32][33][34][35] Here, we examined results of ctDNA assays from over 1,500 plasma samples and found that ctDNA monitoring by dPCR can provide early relapse detection and disease-free corroboration at molecular level during postoperative CRC surveillance as compared to conventional CTS and CEA monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The dPCR assay for quantitative monitoring of ctDNA levels was performed as described previously. [32][33][34][35] Briefly, specific primers and probes labeled for wild-type and mutant alleles were specifically designed for each mutation identified in a primary tumor, using Hypercool Primer & Probe™ technology (Nihon Gene Research Laboratories, Sendai, Japan). For frequently recurring missense mutations, commercially available primer/probe sets were used (Thermo Fisher Scientific, Waltham, MA and Quantdetect, Inc, Tokyo, Japan).…”
Section: Panel Sequencing Of Primary Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTC analysis can theoretically provide more comprehensive and representative information regarding tumor deposition; however, it also has many clinical limitations. Because the content of CTCs in peripheral blood is very low, further exploration is needed in order to learn how to effectively reduce background cells, efficiently enrich CTCs, and improve the accuracy of CTC detection [ 17 ]. CTCs are generally tumor cells that fall off from the primary focus, metastasis, or surgery and enter the peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…ctDNA, small nucleic acids released by apoptotic or necrotic tumor cells, is a type of cfDNA and encodes the genes of tumor cells [ 23 ]. Most ctDNA fragments are double-stranded fragments with a length of 160–200 base pairs, which is roughly the same as the length of nucleosomes [ 17 ]. The amount of ctDNA entering the blood is affected by many factors, such as tumor location, size, metastasis, vascular infiltration, tumor status, and stage.…”
Section: Introductionmentioning
confidence: 99%